SYMEON METAPHRASTES AND THE SEVEN HOMILIES OF MACARIUS OF EGYPT - Marriott, G. L. (The journal of theological studies, 1916)
G. L. MARRIOTT; SYMEON METAPHRASTES AND THE SEVEN HOMILIES OF MACARIUS OF EGYPT., The Journal of Theological Studies, Volume os-XVIII, Issue 69, 1 October 1916,